DYNAMICS OF COVID-19 IN KUZBASS - Рожкова, Кристина Кирилловна; Вавин, Григорий Валерьевич; Елгина, Светлана Ивановна; Мозес, Вадим Гельевич; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Medicine in Kuzbass, 2022)
In Russia, according to Rospotrebnadzor, in 2020, the incidence of airborne infections amounted to 98.6 % among all infectious diseases, of which 90.2 % are ARVI and influenza. Kuzbass, like the whole world, is facing a global challenge – a pandemic of a new coronavirus infection. In the structure of forms of diseases, community-acquired pneumonia accounts for 30.4 % of patients with a new coronavirus infection (COVID-19) at the end of the year. The share of imported cases accounts for 1.9 %. Contact diseases account for 18.0 %. The source was not established in 80.1 % of patients. In the structure of cases, about 50.0 % are the working population. Diseases were registered in all age groups.
Keywords: COVID-19; children from 0 to 18 years old; adult population